The Genus Tithymalus Gaertn. in Northern Caucasus - A. A. Terekbaev; A. A. Teimurov (Юг России: экология, развитие, 2015)
In article data on specific of sort Tithymalus in the North Caucasus are resulted. Geographical diffusion of its kinds on flora areas is analyzed.